Assessing the Performance and Economic Impact of Islamic Finance in the Horn of Africa: A Comparative Study. - Hariri, Rami; Mansour, Nadine (Sharia Oikonomia Law Journal, 2025)
Islamic finance has developed as an alternative to traditional financial systems, acquiring acceptance throughout the Horn of Africa due to its adherence to ethical and faith-based principles. The study assesses the effectiveness of Islamic finance in supporting economic growth, financial inclusion, and social development using a thorough analysis of financial data, economic indicators, and case studies. The study used a Simultaneous Equations Model (SEM) technique with panel data obtained from five Horn of Africa countries: Ethiopia, Somalia, Kenya, Sudan, and Djibouti from 2013 to 2022. The major findings demonstrate that Islamic finance has a positive and significant impact on economic growth, but a positive but insignificant impact on financial inclusion. This study suggests that governments in the sampled countries continue to strengthen the growth of Islamic financing in order to create greater developmental chances and gains, particularly through more inclusive economic growth. The regional government should provide concrete support for Islamic banking and finance operations through a strong institutional framework and long-term political backing.Islamic finance has enormous potential to foster long-term economic progress in the Horn of Africa. Targeted policy reforms and strategic investment decisions can help to unleash this potential, promoting growth, eradicating poverty, and achieving financial inclusion throughout the region.